Development and experiment of the Internet-based telesurgery with MicroHand robot. (February 2018) - Su, He; Li, Jinhua; Kong, Kang; Li, Jianmin
Robot-assisted telesurgery can perform complex surgical manipulations from remote locations. Against the requirements of remote controlling for minimally invasive laparoscopic surgery robot, a prototype telesurgery system integrated on the existing "MicroHand S" robot was built. The prototype worked with the Internet, and a telesurgery communication protocol was set up based on Transmission Control Protocol/Internet Protocol. The stereo images of laparoscopy were transmitted by a hardware-based H.264 encoder/decoder. A demonstration environment of robot-assisted remote minimally invasive surgery between the medical robot laboratory of Tianjin University and the visual surgery laboratory of the PLA Rocket Force General Hospital, which is about 150 km away, was set up. Control signal and laparoscope image transmission test between these two places were conducted. After the pegboard task and knot-tying task of phantom training, the first remote gall bladder removal surgery on the sow of China was successfully performed, on the basis of remote surgery robot system integration. The experimental results show that the developed prototype telesurgery system has enough remote control performance and operability for telesurgery.